1996
DOI: 10.1037/0021-843x.105.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Unacknowledged versus acknowledged rape victims: Situational factors and posttraumatic stress.

Abstract: Investigators of sexual assault have found that a substantial number of women who have been raped do not conceptualize their experiences as such. The present investigation examined differences between 40 unacknowledged rape victims and 20 women who acknowledged their experience as rape in a sample of college women, as well as a control group of 23 nonvictims. Groups were compared in terms of situational factors, postassault symptomatology, defense mechanisms, dissociative disorders, and sexual revictimization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
194
7

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(223 citation statements)
references
References 20 publications
22
194
7
Order By: Relevance
“…Thus, asking men specifically about rape does not identify additional perpetrators. This corresponds to past research with victims and perpetrators, which indicates that few label these events as rape, perhaps because they do not fit the prototypic rape involving a sudden physical attack by a stranger [Falk, 1998;Layman et al, 1996].…”
Section: Self-reported Rates Of Sexual Assault Perpetrationsupporting
confidence: 74%
“…Thus, asking men specifically about rape does not identify additional perpetrators. This corresponds to past research with victims and perpetrators, which indicates that few label these events as rape, perhaps because they do not fit the prototypic rape involving a sudden physical attack by a stranger [Falk, 1998;Layman et al, 1996].…”
Section: Self-reported Rates Of Sexual Assault Perpetrationsupporting
confidence: 74%
“…Cascardi, Riggs, Hearst-Ikeda, and Foa (1996) reported that women raped in locations rated as safe and women attacked by dangerous assailants had more PTSD even when assault brutality was controlled. Layman, Gidycz, and Lynn's study of college women showed that acknowledged rape victims experienced more forceful assaults, resisted more, demonstrated clearer refusal to the attacker, and reported more PTSD symptoms (Layman et al, 1996). In a convenience sample of 102 communityresiding rape survivors (Campbell et al, 1999), neither victim demographics nor rape characteristics were associated with posttraumatic stress symptoms, but victims of known attackers who received few community services and experienced high secondary victimization postassault had more symptoms.…”
mentioning
confidence: 98%
“…Numerous studies have found that the closer an incident is to this script, the more likely it is to be labeled as rape. For example, women are more likely to label the incident as rape if the perpetrator was a stranger or barely known acquaintance (Kahn, Jackson, Kully, Badger, & Halvorsen, 2003;Koss et al, 1988), if it involved physical force, if they resisted physically, if a weapon was used, or if they sustained an injury (Bondurant, 2001;Fisher et al, 2003;Kahn & Mathie, 2000;Layman et al, 1996;Littleton et al, 2009;McMullin & White, 2006). Conversely, women are less likely to label the incident as ''rape'' if it was perpetrated by a romantic partner (Kahn et al, 2003) or if they had been under the influence of alcohol during the experience (Botta & Pingree, 1997;Layman et al, 1996).…”
Section: Factors Associated With Labeling Incidents As Rapementioning
confidence: 99%